THE EFFECT OF PARENTAL ATTENTION, STUDENT LEARNING MOTIVATION, AND SOCIAL ENVIRONMENT ON MATHEMATICS LEARNING OUTCOMES OF GRADE VIII STUDENTS OF SMP NEGERI 2 TANAH MERAH - Givanni Bulan Alfridha Saragih; Ronaldo Kho; Irfan Wahyudi (Penelitian dan Pengembangan Ilmu, 2025)
This study aims to analyze the influence of parental attention, student learning motivation, and the social environment on the mathematics learning outcomes of eighth-grade students at SMP Negeri 2 Tanah Merah. The research employed an ex post facto quantitative approach with simple random sampling, using a questionnaire as the primary instrument. The questionnaire measured three key variables: parental attention, student learning motivation, and the social environment. The findings indicate that each of these variables has a positive and significant influence on students’ mathematics learning outcomes. Furthermore, when examined simultaneously, parental attention, learning motivation, and the social environment collectively contribute to improving students’ achievement in mathematics. These results highlight the importance of family involvement, internal motivation, and supportive social surroundings in enhancing students’ academic performance.